Korelasi Antara Self-Efficacy dengan Kompetensi Klinik Pada Mahasiswa Keperawatan Dalam Praktik Klinik - Sidaria, Sidaria; Murni, Dewi; Maisa, Esthika Ariany; Nelwati, Nelwati (Universitas Fort De Kock Bukittinggi, 2024)
Background: Clinical learning has a very important role in determining the quality of nursing students' learning achievements, because clinical knowledge and skills are the main foundation in clinical education. Nursing students are expected to have competency in the knowledge and skills to provide high quality and safe nursing care to patients, however there are still many nursing students who feel they are not ready to become nurses in the future because they feel they are not yet competent in carrying out nursing care to patients. The aim of the research is to see the correlation between self-efficacy and the clinical competence of Nurse Professional Education students. Methods: This research used correlation research and the sample in this research were clinical practice students of the Nursing Professional Education who had undergone 2 clinical learning stages in semester 1 which were taken using a total sampling technique. Data analysis using SmartPLS. Results: From the research results, it was found that self-efficacy had a positive effect on clinical competence (P Value 0.000, T Statistics 14.273, sample mean 0.686). Self-efficacy influences clinical competence by 46.3% (R Square 0.463), the remainder is influenced by other factors not studied. Conclusion: These findings emphasize the importance of self-efficacy in forming and improving students' clinical competence. By having high self-confidence in their abilities, students are more likely to be able to apply their knowledge and skills effectively in clinical practice.